KAJIAN SOSIOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL PASUNG JIWA KARYA OKKY MADASARI SERTA RELEVANSINYA SEBAGAI MATERI AJAR DI SMA - Nevi Mustikasari; Edy Suryanto; Sri Hastuti (Universitas Sebelas Maret, 2019)
The form of this research is qualitative descriptive used an approach of sociology literature. Data collection technique used: (1) document analysis technique which is novel Pasung Jiwa; (2) interviews technique with informant which are teacher and student. The collected data analyzed by interactive analysis model. The result of the research are: (1) Intrinsic element analysis of novel Pasung Jiwa, the main theme are freedom and the struggle against injustice. The figures analyzed the main character that are Sasana and Jaka, and the additional characters that are Ayah, Ibu, Cak Man, Masita, Banua, Memed and Leman, the Marjinals, Elis, and Kalina . The plot of novel Pasung Jiwa is chronological plot. The background scene happen in Jakarta, Malang, and Batam. The background time happen in 1993-2003. The view point used first person perspective; (2) Social criticism in novel Pasung Jiwa includes social criticism of government because of Orde Baru repressive government. Social criticism of arbitrary power. Social criticism of the economy because of monetary crisis. Social criticism of human rights because of Sasana’s struggle as a transgender; (3) The education value contained within novel Pasung Jiwa are: religious; honest; tolerance; discipline; hard work; creative; independent; democratic; curiosity; the spirit of nationality; love the homeland; appreciate achievement; communicative/friendly; love peace; like to read; social care; and responsibility; and (4) Novel Pasung Jiwa has a novel suitability criteria that can be used as teaching material